Permanent Rose - McKay, Hilary (Margaret K. McElderry Books, 2005)
While trying to reconnect with her friend Tom, who has returned to the United States without leaving a forwarding address, eight-year-old Rose inadvertently discovers the identity of her adopted sister Saffy's father.